Microbial phosphorus removal and recovery by struvite biomineralisation in comparison to chemical struvite precipitation in municipal wastewater - Leng, Yirong; Soares, Ana (Elsevier, 2023)
Microbial biomineralisation is attracting significant interest as an innovative process to recover nutrients from wastes. Nevertheless, little is understood about the requirements to form struvite using biological pathways in wastewater and how does this compare with conventional chemical processes. To address this gap, Halobacterium salinarum, Bacillus pumilus, Brevibacterium antiquum, Myxococcus xanthus and Idiomarina loihiensis were grown in wastewater to explore the relationships between cell growth, nutrients levels and properties of the recovered precipitates. The microorganisms were capable of removing ortho-phosphate (PO4-P) from municipal wastewater at concentrations ranging from 5.4 to 62.4 mg PO4-P/L. Visible crystals of biological struvite (bio-struvite) (identified by morphology XRD and elemental analysis), were observed at PO4-P ≥ 19.7 mg/L, compared to chemical struvite precipitation at 62.4 mg/L PO4-P (with pH adjustment). The initial nutrient concentrations presented a strong positive correlation with bio-struvite production yields and crystal size distribution. B. antiquum distinguished itself by relatively stable PO4-P removal (68–97%) independent of the initial nutrient concentration, with effluents containing as low as 1 mg PO4-P/L. The recovered bio-struvite presented high purity with low heavy metal contents, meeting regulations for inorganic fertiliser. The microbial processes for phosphorus (P) recovery as bio-struvite presented several key advantages: bio-struvite crystals were released to the wastewater and recoverable by filtration at PO4-P ≥ 19.7 mg/L, no need to adjust pH, bio-struvite crystals had purity equivalent to 11.8–12.3% P and low heavy metal content, which was similar or better than that of chemical struvite (12.6% P). This study validates bio-struvite’s relevance for low nutrient concentrations.
Keywords: Bio-struvite; Biomineralisation; Chemical precipitation; Fertiliser value; Phosphorus removal; Phosphorus recovery